Performance ofpearlmillet (Pennisetum glaucum) intercoppped with pigeonpea (Cajanus cajan) under varying fertility levels in the rainfed environment of Bundelkhand region - Tripathi, A.K.; Kushwaha, H.S. (Annals of Agricultural Research, 2014)
A field experiment was conducted during rainy seasons of 2004-05 and 2005-06 at Agricultural Research Farm, Nehru P.G. College, Lalitpur (U.P.) in sandy loam soil, to assess optimum NPK doses for enhancing productivity and nutrient uptake of pearlmillet and economic potential and efficiency of pearlmillet + pigeonpea intercropping system. The seed and stover yield of intercrop pearlmillet and pearlmillet equivalent yield and LER were significantly higher with pearlmillet 75% NPK+ pigeonpea RDF compared to sole pearlmillet with RDF. Growth parameters like plant height and leaves/plant and yield attributes viz. panicle girth, seeds/panicle and 1000-seed weight were also remarkebly higher with pearlmillet 75% NPK+ pigeonpea RDF fertility levels. Protein content did not affect significantly due to intercropping system during both the years. Nutrient uptake of pearlmillet in terms of N,P,K was significantly increased under intercropping system.